When Surviving is Not Enough: From Militancy to Collaboration. - Frankel, Emily E. (Chasqui (01458973), 2021)
In the article, the author discusses the militancy and political transformations of activists Marcia Alejandra Merino Vega, Luz Arce Sandoval and María Alicia Uribe Gómez in Chile. Also cited are the political reconciliation efforts between left and right political factions in the country, and the three activists' collaboration with the administration of Augusto Pinochet.